Faster or slower decarbonization? Policymaker and stakeholder expectations on the effect of the COVID-19 pandemic on the global energy transition. (June 2021) - Pianta, Silvia; Brutschin, Elina; van Ruijven, Bas; Bosetti, Valentina
Abstract: The COVID-19 pandemic might have tremendous consequences on decarbonization efforts across the globe. Understanding governments' policy action in the short and medium term is key to assess whether the response to the crisis will crowd out or fast-track decarbonization efforts. We surveyed over 200 policymakers and stakeholders from 55 different countries to collect climate policy expectations in various sectors and regions in the next five years. While support for high-emitting sectors is not expected to dissolve completely, commitment to policies supporting the transition to low-carbon energy and transport sectors is expected to increase substantially. This is true for OECD and Asian countries, representing approximately 90% of global emissions. Our results suggest that expectations that the COVID-19 pandemic will accelerate decarbonization efforts are widely shared.